Uncertainty challenges in service cost estimation for product- service systems in the aerospace and defence industries - Erkoyuncu, John Ahmet; Roy, Rajkumar; Shehab, Essam; Wardle, P. (Cranfield University Press, 2009)
Contracting for availability is expected to become more prevalent for product -service systems (PSS) in the aerospace and defence industries. These contracts tend to transfer responsibilities for the operational phase from the customer to the supplier. In parallel, with operational life spans spanning several decades, the ability to deal with uncertainty in cost estimation for support activities is becoming critical. This paper outlines challenges within this process derived from literature as well as issues that were highlighted during interviews with four major defence and aerospace organisations.
Organised by: Cranfield University
Keywords: Product Service Systems; uncertainty; cost estimation; service